HERODOTOS’TA KÜÇÜK ASYA PERS KRALİYET YOLU: DİĞER ANTİK YAZARLARINKİ İLE KARŞILAŞTIRILARAK İNCELENMESİ VE AÇIKLANMASI. - DEMİR, Muzaffer (Tarih İncelemeleri Dergisi, 2020)
It can especially be understood from the cuneiform documents of MurÅ¡ili II period that there existed a road system dated to the XIII th century BC, which extended from á¸ªattuÅ¡a, the capital of the Hittites, to the cities of Millawanda (Miletus?) and ApaÅ¡a (Ephesus?) in Western Anatolia. This road network became much more important when the Persians took over the capital of the Lydians, Sardis, in 547 BC and made it a satrap center in Western Anatolia. This road network, starting from the central Sardis and extending to Persian capital, Persepolis, in the east, was healed with political, administrative and commercial purposes during the reigns of Persian kings, Great Cyrus (560-530 BC) and the Darius I (522-486 BC) and as a result of this it was was called as â€œThe Persian royal roadâ€. Since the Persian sources related to this subject are insufficient, most of the data related to this road system is obtained and interpreted from the ancient Greek writers in general and from the Roman writers in partial. In this study, we will compare the texts about the Persian royal road and try to make a suggestion for the main route over which the express mail service operated by mainly referring to the related works of Herodot, Xenophon, Cicero and Strabo as well as the biography of Hadrian in Historia Augusta